Lentiviral vector transduction of spermatozoa as a tool for the study of early development. Issue 1 (3rd March 2014) - Chandrashekran, Anil; Isa, Ihsan; Dudhia, Jayesh; Thrasher, Adrian J.; Dibb, Nicholas; Casimir, Colin; Readhead, Carol; Winston, Robert
Abstract : Spermatozoa and lentiviruses are two of nature's most efficient gene delivery vehicles. Both can be genetically modified and used independently for the generation of transgenic animals or gene transfer/therapy of inherited disorders. Here we show that mature spermatozoa can be directly transduced with various pseudotyped lentiviral vectors and used in in vitro fertilisation studies. Lentiviral vectors encoding Green Fluorescent Protein (GFP) were shown to be efficiently processed and expressed in sperm. When these transduced sperm were used in in vitro fertilisation studies, GFP expression was observed in arising blastocysts. This simple technique of directly transducing spermatozoa has potential to be a powerful tool for the study of early and pre‐implantation development and could be used as a technique in transgenic development and vertical viral transmission studies. Abstract : Sperm are mature cell types that can be transduced by lentiviral vectors. Lentiviral integration in sperm has been demonstrated. Lentivirally transduced sperm is useful for the study of early development.